Influence of grain boundary segregation on the deformation behavior of nanocrystalline Ni50Co50 solid solution alloys investigated by molecular dynamics simulations - Rui Liu; Luyao Cheng; Liang Chen; Jinfu Li; Lingti Kong (Journal of Materials Research and Technology)
Molecular dynamics simulations were carried out to investigate the tensile deformation behavior of Ni50Co50 solid solution nanocrystalline alloys with varying degrees of grain boundary segregation. A comprehensive analysis disclosed that the observed strengthening in the Ni-rich grain boundary model is primarily due to the formation of Lomer-Cottrell locks and dislocation networks which impede dislocation motion. Plastic deformation, on the other hand, is predominantly governed by enhanced grain boundary migration, grain rotation, and deformation twinning. In the Co-rich grain boundary model, the interactions among twins, dislocations, and grain boundaries, stemming from the formation of extensive stacking faults and twinning, dictate the plastic deformation and strengthening. Fluctuations in grain boundary composition promote stress concentration, thereby facilitating plastic deformation and dislocation accumulation within the grain, which in turn enhances strain hardening. The study reveals that the Ni50Co50 solid solution nanocrystalline alloys exhibit both high tensile strength and favorable plasticity for models with grain boundary segregation around ±10%. These insights provide valuable guidance for the development of Ni50Co50 nanocrystalline alloys with optimized strength and toughness.